THE IMPROVEMENT OF LOW-WASTE TECHNOLOGIES OF WORKING BODY OF WATER PREPARATION AT THERMAL AND NUCLEAR POWER PLANTS - K. D. Rymasheuskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
In the present work the main directions of water desalination technologies improving have been analyzed. Possible techniques of high-quality treatment of water that enable the reduction of amounts of environmentally hazardous substances to be discharged into the hydrosphere are indicated. The purpose of the work was to improve the ecological efficiency and the effectiveness of water treatment equipment at heat power plants when designing new and the modernizing existing water treatment schemes. In order to achieve this goal the following problems have been solved: the one of analyzing the main directions of the improvement of technologies of working body of water preparation at thermal and nuclear power plants; of analyzing the main directions of reduction of total volume of highly mineralized power plant wastewaters; of developing the technological scheme of recycling of concentrate of membrane installations and regenerants of ionite filters in acid and alkali; of developing the technological scheme of transformation of the sludge in pre-processing waste into valuable commodity products. The results of research can be applied for the design of new and the modernization of existing water treatment installations of thermal and nuclear power plants. It will enable to reduce considerably the use of natural water and the amount of chemicals added as well as the volume of wastewater and the concentration of dissolved solids in it. As a consequence, the negative impact of thermal and nuclear power plants on the hydrosphere will be reduced.